Perancangan Rute Distribusi Barang Menggunakan Metode Nearest Neighbour Pada CV Lima Jati - Juniwati; Devi Rosita; Lina Aulia (Jurnal Serambi Engineering, 2025)
A company must be effective and efficient in determining distribution route to saving distance and transportation cost in shipping goods. Distribution routes that are not optimal can cause delay in delivery and company has to spend higher cost for distribution. CV Lima Jati has problem in determining an optimal distribution route to deliver goods to customers. This research was conducted to design an optimal distribution route with minimum distance and distribution cost. Nearest Neighbour method can be applied to obtain an optimal solution to solve the problem. The data used consist of demand customers, distance between customers, distribution cost and vehicle capacity. The result shows an optimal distribution route with total distance 303,5 kilometers or 54,4% from existing total distance. Distribution cost total is Rp 387.618 or decrease 29%. The conclusion is an optimal solution which is efficiency total distance and distribution cost after designing distribution route by using Nearest Neighbour method.